Pengaruh Brand Image, Kualitas Produk Dan Brand Ambassador Terhadap Keputusan Pembelian - Sandradewi, Made Dita Pramesti; Nurlinda, R. A (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research tests and analyzes the influence of brand image, product quality, and brand ambassador simultaneously and partially on purchasing decisions to determine the dominant variables that influence purchasing decisions. This research uses quantitative data with primary data obtained through distributing questionnaires using Google Forms. This research used a sample of 200 respondents with the criteria of having purchased. It used Nike shoes, having seen Kevin Durant as a brand ambassador, aged > 17 years, residing in the Jabodetabek area. The collected questionnaires will be measured using the three-box method and tested for suitability using validity and reliability tests. The data analysis technique used is the multiple linear regression test. Based on the analysis results, it is known that the variables brand image, product quality, and brand ambassador simultaneously and partially have a positive effect on purchasing decisions. Furthermore, the results show that brand image is the most dominant variable influencing purchasing decisions. It is hoped that the results of this research can be a reference for the Nike company to strengthen the brand image of its products. A strong brand image can increase the program’s success in attracting or re-engaging new consumers.